Following Glaziou’s footsteps: rediscovery and updated description of three species of Behuria Cham. (Melastomataceae) from the Atlantic Forest (Brazil) - Bochorny, Thuane; Bacci, Lucas F.; Goldenberg, Renato (Phytotaxa, 2017)
This study was carried out in the state of Rio de Janeiro and led to the rediscovery of three endemic and threatened species of Behuria (Melastomataceae). The type specimens for these species were collected by the French botanist A.F.M. Glaziou. Behuria corymbosa and Behuria glazioviana were collected for the last time 127 years ago by him, in 1889. Behuria mourae was collected twice after the type; the last collection dates from about 72 years ago. In order to find the exact localities where Glaziou collected these three species we studied the labels of the type specimens, Glaziou’s notebooks and letters, looking for tracks that would lead us to places that he visited. We also consulted documents from a local library and gathered information from local people. Here we present updated descriptions, comments, photos and conservation assessments for each species.